CONCEPTUAL FIELD OF THE CONCEPT “HUMAN” IN ENGLISH AND UZBEK - Yusupova, Dilafruz; Solijonov , Mukhammadjon (Educational Research in Universal Sciences, 2023)
The purpose of the article is to analyze the conceptual field "human" in English and Uzbek languages from the point of view of the Modern Linguistics.